PENCAPAIAN PERKEMBANGAN SENI ANAK USIA 0-6 TAHUN - Septiyaningrum, Dina Rus; Aprilia, Cindy; Faisal, Vava Imam Agus (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
Child after early is them which is have age to under 6 year of is including which still reside in in content which is being in growth process and growth of physical, bouncing, personality and is intellectual of him both for served and also do not serve in institute education of age child early. Growth of art represent wrong human being masterpiece and also kreatig stimulasi, its meaning involve in study art can activate the more areas in brain from at without